Overcoming jurisdictional immunities a remedies framework for employees of international organizations in the Philippines (2021)
For decades, domestic courts, including Philippine courts, have denied appropriate remedy to employees of intemational organizations ("IO") whose rights were breached in the course of official duties, in favor of the functional necessity doctrine and the State obligation to grant I0 immunity arising from treaties. This Note contributes to the literature of I0 immunities and employees' rights by arguing that the State obligation to ensure the rights (1) to equality before courts and tribunals and (2) to a fair and public hearing by a competent, independent, and impartial tribunal of persons, the I0 employees in particular, under Article 14 (1) of the International Covenant on Civil and Political Rights, may not be unduly restricted by treaty obligations granting I0 immunity. While recognizing the concurrent treaty obligations pursuant to the principle of pacta sunt servanda, it explores the potential of the Philippine legal concept of judicial review in relation to grave abuse of discretion as a basis to penetrate I0 immunity, in cases where the ICCPR rights of I0 employees are undermined. Informed by trends in other jurisdictions and by the progressive development of intemational law, this Note proposes a framework of analysis for Philippine domestic courts to overcome the jurisdictional bar of I0 immunity and to provide remedies to employees that are adequate and compliant with intemational human rights law. Lastly, this note seeks to explore policy and legal considerations faced by the Philippines in affording remedy to aggrieved IO employees.
Keywords: International organization; International Covenant on Civil and Political Rights (1966 December 16); Employee rights